The Normative Significance of Aristocratic Constitutions in Aristotle’s Politics - Irrera, Elena (ΠΗΓΗ/FONS, 2016)
This paper contends that, despite evidences, Aristotle’s view of aristocratic constitutions displays a heavily marked normative content. I argue that his understanding of aristocracy may be separated into four main strands: (i) an ideal type, based on the rotation of power of virtuous people over equally virtuous citizens (as evinced from a joint reading of Books III and IV); (ii) a type grounded on a fine blending of social classes, as emerging from a reading of Pol. IV, 7.1293b7-18 in the light of Politics IV,3.1290a24-29; (iii) a polity inclining toward oligarchy, which seems to lack any normative worth; (iv) an ‘aristocratic polity’, grounded on the political role of the middle class (Book IV.11). I shall propose that, in non-ideal conditions, type (iv) is the constitution which best accommodates (a) the need for stability and concord, (b) the search for an ideal of structural harmony and proportion among rulers and citizens.